แนวทางพัฒนาการบริหารคนเก่งของโรงเรียนในสังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐานในกรุงเทพมหานคร - ภาคี เดชตรัยรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The purposes of this quantitative research were 1) to study the actual state and the desirable state of talent management in Schools under the Office of the Basic Education Commissions in Bangkok.  2) present the approaches for development of talent management in schools under the office of the basic education commissions in Bangkok.  The sample groups were consisted of 463 people comprised of Director of the School, Deputy Director of Human Management and Senior Professional Level Teachers (K 3 Teachers) and higher conventional in the schools.  Questionnaire was the tool for collecting of data to study the actual state and the desirable state of the management of talent.  The methods of analyzed data were frequency, percentage, average, standard deviation, and Priority Needs Index (PNImodified).  The research results were found that 1. The highest the actual state of talent management in schools was talent development, talent retention, and the third was reward & recognition. 2. The highest the desirable state of talent management was talent retention, talent development, and the third was reward & recognition. 3. The approaches for development of talent management are 7 approaches are 1) when talented teachers have outstanding performance, director of the school should give praise to them.  2) Director of the school should inform talented teachers about policies, guidelines and strategies of school.  3) Director of the school should create a strategy to raise salaries for talented and other teachers.  4) Director of the school should formulate talented management stetegy maching with the goals, policies and directions of the school.  5) Director of the school should have a policy to encourage talented teachers to think progressively develop themselves according to their abilities.  6) Director of the school should create a supportive environment and encourage all teachers to show their full potential.  7) Director of the school should assigned talented teachers to join both internal and external training, or participate other activities.